Merkel Cell Carcinoma: A Comparison of Different Immunohistochemical Markers Useful in Diagnosis - Cizenski, MD, Jeffrey; Muhlbauer, MD, Aaron; Xu, Helen; Helm, MD, Thomas (North American Journal of Medicine and Science, 2018)
Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine carcinoma associated with a high mortality rate. A polyomavirus integrated into the genome of most tumors is thought to be pathogenic. MCCs may be difficult to distinguish from other small cell carcinomas, melanoma, lymphoma, and others. Immunohistochemical marker studies are essential for accurate and efficient diagnosis. Although the paranuclear dot-like pattern seen with staining for cytokeratin 20 is considered characteristic, antibodies directed at other cytokeratins such as cytokeratin 8 (CAM 5.2), pancytokeratins (AE1/AE3), and other clones that recognize low molecular weight cytokeratins are also useful for diagnosis. We set out to evaluate which stains are helpful in diagnosing the cases of MCC encountered in our patient population. A retrospective study of 59 cases of MCC from our files was performed. Each MCC was stained with a panel of IHC markers and evaluated for the staining pattern and intensity in an effort to identify the most efficient IHC stains useful in establishing a diagnosis of MCC. [N A J Med Sci. 2018;11(1):34-38. DOI: 10.7156/najms.2018.1101034]